Trust as a factor activating implementation abilities – from theory to practice of a flexible company - Nogalski Bogdan; Niewiadomski Przemysław (Management, 2017)
As a result of the wide recognition of the importance of trust as an element related to the cooperation in a variable and hardly predictable environment, the trust was appreciated by management sciences. Thanks to the trust, the organisation can react quickly to changes in a complex and turbulent environment, in which it is necessary to develop new - adequate to the needs - products. In the context of the above, the research was commenced, whose execution was the condition of an attempt to answer the question: is the number of the products implemented by the manufacturer a derivative of trust built between him/her and his/her recipients? In the context of such a question, the main objective of the paper is an attempt to illustrate trust - created by the manufacturer - as an attribute promoting his/her implementation flexibility. The achievement of such an objective is possible thanks to a detailed case analysis of the selected implementation process, which confirms that good relationships between partners - as a result of the increase in production series - may imply a decrease in its unit costs, which leads to significant profits in the long term.